Development of authentication code based on spectral amplitude coding optical code division multiplexing for multi-user pseudo quantum key distribution - Abiola, Taiwo Ambali (2018)
Quantum Key Distribution (QKD) has remained the provable technique of ensuring secure communication amidst the impending security threat by the emerging quantum computers. Its security guarantee is based on superposition and entanglement, which are fundamental principle of quantum mechanics. As efforts are currently underway toward actualization of QKD network, researchers have explored a number of techniques though which this could be achieved. Some of the techniques proposed are; subcarrier based QKD network, Orthogonal Frequency Division Multiplexed (OFDM) based QKD network and spectral amplitude coding optical code division multiplexed (SAC-OCDMA) based QKD network. Among the aforementioned technique, SAC-OCDMA based system has history of efficient channel management, asynchronous nature, as well as channel security. Nevertheless, the adopted Optical Orthogonal Code (OOC) which is a family of OCDMA code, has a couple of challenges which include complex architecture, as well as longer code length, both of which are capable of resulting to reduction in the secure key rate and number of simultaneous users. Thus, this work presents a new one-weight authentication code, which are assigned, uniquely to individual user in SAC-OCDMA based QKD network. The performance of the code was explored in QKD network using simulation, mathematics and laboratory experiment. Firstly, the proof of concept of plug and play (p&p) in QKD network was carried out and the concept of phase reorientation was clearly established using Optisystem simulation tool. This was followed by mathematical modelling of the secure key rate and QBER for different number of users. As observed in the obtained results, at an average mean photon number of 0.48, a 21-user network was achieved at a secure key rate of 24 bps over a distance of 5 km. The result of comparison of the proposed code with a Wavelength Division Multiplexed (WDM) system shows its security capability above the later. The code was further compared with an OOC based network and found to generate key at higher rate when the number of users is below 14. A two-user experimental result shows the real life realization of the proposed system as a transmission distance up to 40 km was achieved with secure key rate of 320 bps. Application of the proposed code in Differential Phase Shift Key – Quantum Key Distribution (DPS-QKD) environment was also established. The obtained results have shown that aside presenting a secure mechanism, the design flexibility and moderate code length exhibited by the proposed code are excellent factors that could be explored in enhancing the performance of QKD network.